Did Chinese Buddhists translate the old formula ‘him I call a Brahmin’? The reconstruction of Buddhism as the path of nirvāṇa in Early Chinese translations - Villamor Herrero, Efraín (Estudios de Traducción, 2024)
At first, Chinese translators lacked a unified criterion for interpreting Buddhist scriptures. They employed various phonetic transliterations and gradually adopted etymological approaches as their understanding developed. This study analyzes the Chinese translations of the oldest stratum of Pāli scriptures, focusing on the formula 'him I call a Brahmin', attributed in the Canon as the words of the Buddha. This formula has been preserved in Chinese Buddhist scriptures as well. However, Chinese translators did not always translate the formula literally. Their goal was to persuade Chinese readers that they were knowledgeable about the path of nirvāṇa.